Reproductive health services for Syrian refugees in Zaatri Camp and Irbid City, Hashemite Kingdom of Jordan: an evaluation of the Minimum Initial Services Package. Issue 1 (December 2015) - Krause, Sandra; Williams, Holly; Onyango, Monica; Sami, Samira; Doedens, Wilma; Giga, Noreen; Stone, Erin; Tomczyk, Barbara
Abstract Background The Minimum Initial Services Package (MISP) for reproductive health, a standard of care in humanitarian emergencies, is a coordinated set of priority activities developed to prevent excess morbidity and mortality, particularly among women and girls, which should be implemented at the onset of an emergency. The purpose of the evaluation was to determine the status of MISP implementation for Syrian refugees in Jordan as part of a global evaluation of reproductive health in crises. Methods In March 2013, applying a formative evaluation approach 11 key informant interviews, 13 health facility assessments, and focus group discussions (14 groups; 159 participants) were conducted in two Syrian refugee sites in Jordan, Zaatri Camp, and Irbid City, respectively. Information was coded, themes were identified, and relationships between data explored. Results Lead health agencies addressed the MISP by securing funding and supplies and establishing reproductive health focal points, services and coordination mechanisms. However, Irbid City was less likely to be included in coordination activities and health facilities reported challenges in human resource capacity. Access to clinical management of rape survivors was limited, and both women and service provider's knowledge about availability of these services was low. Activities to reduce the transmission of HIV and to prevent excess maternal and newborn morbidity and mortality were available, although some interventions needed strengthening. Some planning for comprehensive reproductive health services, including health indicator collection, was delayed. Contraceptives were available to meet demand. Syndromic treatment of sexually transmitted infections and antiretrovirals for continuing users were not available. In general refugee women and adolescent girls perceived clinical services negatively and complained about the lack of basic necessities. Conclusions MISP services and key elements to support implementation were largely in place. Pre-existing Jordanian health infrastructure, prior MISP trainings, dedicated leadership and available funding and supplies facilitated MISP implementation. The lack of a national protocol on clinical management of rape survivors hindered provision of these services, while communities' lack of information about the health benefits of the services as well as perceived cultural repercussions likely contributed to no recent service uptake from survivors. This information can inform MISP programming in this setting.